2011
DOI: 10.1370/afm.1297
|View full text |Cite
|
Sign up to set email alerts
|

Translating Cholesterol Guidelines Into Primary Care Practice: A Multimodal Cluster Randomized Trial

Abstract: PURPOSE We wanted to determine whether an intervention based on patient activation and a physician decision support tool was more effective than usual care for improving adherence to National Cholesterol Education Program guidelines.METHODS A 1-year cluster randomized controlled trial was performed using 30 primary care practices (4,105 patients) in southeastern New England. The main outcome was the percentage of patients screened for hyperlipidemia and treated to their low-density lipoprotein (LDL) and non-hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(65 citation statements)
references
References 51 publications
0
56
0
9
Order By: Relevance
“…Five studies reported that participants thought guidelines could be used as a simple tool to provide health information and recommendations which could lead to a better understanding of their health [15,16,21,22,38]. However, surveys conducted by SIGN and NICE found that only 8% of respondents thought guidelines were used to inform the public or dealt with advice for patients [30,34].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported that participants thought guidelines could be used as a simple tool to provide health information and recommendations which could lead to a better understanding of their health [15,16,21,22,38]. However, surveys conducted by SIGN and NICE found that only 8% of respondents thought guidelines were used to inform the public or dealt with advice for patients [30,34].…”
Section: Resultsmentioning
confidence: 99%
“…The update search (January 2011 through October 2012) identified 14 articles representing 13 unique studies. 8194 Of these, seven studies 81–87 met the inclusion criteria; however, one study 86 was judged to be of limited quality and therefore excluded from analysis. From the combined searches, a total of 45 studies 2434,36–39,4148,50–56,58,60,61,63,6568,8085,87 qualified for analysis in this review.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Nineteen studies 25,34,36,39,44,4648,51,53–55,58,60,61,63,82,84,87 were conducted in practices with an academic affiliation, and three studies 25,28,80 took place in Veterans Affairs facilities. Studies focused on screening for CVD risk factors (six studies) 36,42,43,48,66,67 ; hypertension management (seven studies) 25,33,37,39,50,51,63 ; lipid management (six studies) 24,27,33,68,81,84 ; and diabetes management or CVD prevention among a diabetic population (15 studies). 26,29,30,38,41,44,45,47,52,58,60,65,82,85,87 Further, 11 studies 28,31,32,34,46,53–56,61,80 addressed other disease areas in addition to CVD prevention.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations